Menumbuhkan Kesadaran Hidup Ekologis melalui Komunikasi Lingkungan di Eco Learning Cam - Santi Susanti; Tine Silvana Rachmawati (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2018)
This study aims to reveal the forms of environmental communication applied at Eco Learning Camp or Eco Camp Bandung in fostering awareness of ecological life. Eco Camp is a non-profit institution that aimed to build public awareness to preserve nature and live in harmony with nature as a fellow creation of God. The method used is descriptive qualitative, in the form of observations of experienced situation and interviews with Eco Camp managers. This research resulted in findings ; Eco Camp has seven new awareness of ecological life that is applied in daily life in the Eco Camp environment, starting from the internal environment of its management, since waking up until before going to bed. The activities is expected to emerge awareness of the importance of maintaining good relations with nature, so that nature provides good reciprocity for humans. The conclusion of this study is that attractive and patterned enviromental communication in an institution that cares about the environment can contribute to the emergence of awareness to maintain good relations between humans and natural environment.